Ali al-Sayis's Attitude toward the Qira'at Sab'ah in Tafsir ayat al-Ahkam: A Methodological Analysis - Fahmi, M.; Mahfud, Ahmad; Salim, Moh. Fuad (QiST: Journal of Quran and Tafseer Studies, 2025)
This study examines Ali al-Sayis's stance toward the Seven Qira'at in Tafsir ayat al-Ahkam, with a focus on methodological analysis and its implications for the interpretation of Islamic legal verses. The primary issue addressed is the lack of in-depth research on how Ali al-Sayis integrates the variant readings of the Seven Qira'at into the process of legal derivation (istinbaṭ al-ahkam), despite the significant potential of qira'at in shaping the meaning of legal verses. The study aims to critically assess Ali al-Sayis's approach and methodology in responding to the Seven Qira'at and to analyze their relevance and contribution to the construction of contemporary Islamic law. This research employs a qualitative–descriptive method using library research techniques, with Tafsir ayat al-Ahkam as the primary source and Manna' al-Qattan's principles of the Seven Qira'at as the analytical framework. The findings show that al-Sayis adopts a selective yet open approach toward sound qira'at, adhering to the criteria of linguistic eloquence (fasahah), conformity with the 'Uthmanic script (rasm 'Uthmani), and the authority of the transmission chain (sanad). This approach not only demonstrates al-Sayis's methodological depth but also offers important implications for the development of contemporary Qur'anic studies—particularly in positioning qira'at as linguistic instruments that enrich interpretation without violating textual authority. Consequently, the study reinforces the understanding that qira'at can play a significant role in reconstructing modern fiqh in a more adaptive, contextual, and responsive manner to the needs of the present era.